计算:8x^2y^4(-3x/4y^2)/(-x^2y/2)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 16:23:03
计算:8x^2y^4(-3x/4y^2)/(-x^2y/2)计算:8x^2y^4(-3x/4y^2)/(-x^2y/2)计算:8x^2y^4(-3x/4y^2)/(-x^2y/2)8x²y^
计算:8x^2y^4(-3x/4y^2)/(-x^2y/2)
计算:8x^2y^4(-3x/4y^2)/(-x^2y/2)
计算:8x^2y^4(-3x/4y^2)/(-x^2y/2)
8x²y^4(-3x/4y²)/(-x²y/2)
=2x²(-3x)y²/(-x²y/2)
=12xy
计算(x^8-x^7y+x^5y^3-x^4y^4+x^3y^5-x^y^7+y^8)(x^2+xy+y^2)
计算:1/(x-y)-1/(x+y)-2y/(x^2+y^2)-4y^3/(x^4+y^4)-8x^7/(x^8+y^8)
计算(2x-3y)(x+4y)-(3x+y)(x-2y)(2x-3y)(x+4y)-(3x+y)(x-2y)
(x-3y)(y+2x)-(4y-3x)(3x+4y)计算
计算:(x-y)^2*(x+y)^3*(-x-y)^3*(y-x)^4
计算:8x^2y^4(-3x/4y^2)/(-x^2y/2)
计算 (x^8+y^8)(x^4+y^4)(x^2+y^2)(x+y)(x-y)
计算:[(2x - 3y)^2 - (x-y)(4x+2y)] / 2y
计算(3x+y-2)(4x-y+2)
计算(4x^2y-9y)/(2x+3)
计算:3x-2y- [-4x+(z+3y)]
计算:2xy/(x+y)².(x+y)/4y
计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x
计算:(8y^2/x-2y)+(x^2/2y-x)-(4y^2/x-2y)
计算:(1)8x^2y^2*(-3x/4y^5) (2)(x+y)^2/xy-y^2*(y-x)^2/xy+y^2
3x+2=y 5X+4=Y 7X+6=Y 9X+8=y 11x=y要如何计算
计算:(x+3y)(2x-y)
计算:(2x-3y)(x+y)